Comparison of the clinical characteristics of asthma based on methacholine bronchial provocation test sensitivity - Yu-Mi Bang; Young Hee Nam; Seung Eun Lee; Gil Soon Choi; Eun-Jung Jo; Hyo In Rhyou; SungMin Hong; Ho Young Lee; Hongyeul Lee; Chan Sun Park; Mi-Yeong Kim (Allergy asthma & respiratory disease, 2025)
Purpose: Methacholine bronchial provocation tests (MBPTs) are commonly used to assess airway hyperresponsiveness, but some patients show no significant response. This study aimed to compare the clinical characteristics of asthmatic patients based on their sensitivity to MBPTs. Methods: We conducted a retrospective cross-sectional study involving adult asthmatic patients from 6 university hospitals in South Korea. Patients were categorized into 2 groups: those with MBPT sensitivity (the provocative concentration of methacholine that leads to a 20% reduction in forced expiratory volume in 1 second [PC20]≤ 16 mg/mL) and those with lower sensitivity (PC20> 16 mg/mL). Clinical characteristics were compared between the 2 groups. Results: Among 346 patients, 213 had PC20≤ 16 mg/mL and 133 had PC20> 16 mg/mL. The PC20> 16 mg/mL group had a higher prevalence of late-onset asthma (P= 0.024) and obesity (P= 0.045). While no significant differences in immunoglobulin E (≥ 200 IU/mL) were found, the PC20≤ 16 mg/mL group had greater T2-high inflammation, such as elevated eosinophil counts and fractional exhaled nitric oxide (P< 0.001 and P= 0.004, respectively). Asthma exacerbations requiring emergency visits or hospitalizations were more frequent in the PC20> 16 mg/mL group, despite a lower proportion of patients on higher-step treatments according to Global Initiative for Asthma guidelines. Conclusion: Asthmatic patients with PC20> 16 mg/mL tend to present with late-onset asthma, less T2-high inflammation, and higher rates of asthma exacerbations. Further studies are needed to clarify the clinical features of asthma patients with PC20> 16 mg/mL and assess the long-term significance of these findings.